Yak miR‐2285o‐3p attenuates hypoxia‐induced apoptosis by targeting caspase‐3. (22nd November 2021) - Zhang, J.; Long, K.; Wang, J.; Zhang, J.; Jin, L.; Tang, Q.; Li, X.; Ma, J.; Li, M.; Jiang, A.
Summary: miRNAs are a class of hairpin‐derived RNAs, 21–24 nucleotides in length, which are involved in a range of biological processes. The bta‐miR‐2285 family has over 40 members spanning the entire bovine genome. We previously found that bta‐miR‐2285o‐3p was highly expressed in yak heart and lung when compared with cattle, which prompted us to investigate its potential function in high‐altitude adaptation of yaks. In this study, we detected wide‐spread high expression of bta‐miR‐2285o‐3p in yak tissues. Further experiments revealed that the protein tyrosine phosphatase receptor type M ( PTPRM ) gene was the host gene of bta‐miR‐2285o‐3p and that two linked SNPs in bta‐mir‐2285o precursor affected the biogenesis of mature miRNA (bta‐miR‐2285o‐3p). Functional analysis in vitro indicated that bta‐miR‐2285o‐3p attenuated hypoxia‐induced apoptosis by targeting very low‐density lipoprotein receptor ( VLDLR ), phosphatase and tensin homolog ( PTEN ) and caspase‐3. Expression level analysis in vivo revealed the high negative Pearson's correlation between bta‐miR‐2285o‐3p and caspase3 in yak, highlighting the potential important roles of bta‐miR‐2285o‐3p in yak high‐altitude adaptation. Our study provides a typical model for deciphering the function of miRNAs in environmental adaptation.